Adaptive teaching of Fractions: A comparative educational approach in the United States and Spain (Revista Universitaria del Caribe, 2026)
This comparative examination considers the conceptualization and enactment of adaptive instruction of fractions in the United States and Spain, exploring systemic, cultural, and pedagogical factors affecting instruction. Fractions, a cornerstone of math literacy, are challenges worldwide due to traditionally procedural teaching. Adaptive instruction—adjusting content, pace, and support—has arisen to meet more diverse learner needs.The study employs curriculum analysis, classroom observations, teacher interviews, and surveys of 12 schools in both countries. Results are found that American schools adopt more systemic adaptive strategies like Response to Intervention (RTI), differentiated instruction, and technology. Spanish schools emphasize inclusive ideologies but without ongoing practice, especially fraction-specific content.American teachers had improved access to professional development training and teaching resources, while Spanish teachers were limited by enormous class sizes and inflexibility in the curriculum. Both teachers identified adaptation as a high value and referred to barriers like time, training, and support. In both nations, students responded positively to adaptive practices, with greater engagement and assertiveness when instruction included visual illustrations, formative assessment, and contextual problem-solving.